Identificação em malha fechada para controle tolerante a falta passivo aplicado a um sistema industrial de bombeamento hidráulico - ROCHA, Erick Melo (Universidade Federal do Pará, 2020)
Fluid pumping systems are part of many industrial applications. From the traditional water supply, to the cooling systems of thermonuclear power plants and the complex aircraft maneuvering system, using pneumatic actuators, we find examples of application of these systems. As any physical system, fluid pumping systems may also be subject to anomalous behaviors or failures that can lead to malfunction or even loss of stability of an entire process. Such faults may cause permanent damage due to the effect of undesirable phenomena such as cavitation and water hammer, for example. Thereby, this work proposes the development of a Fault Tolerant Control System (FTCS) aiming at to mitigate the undesirable effects of pressure oscillation and speed variation that may affect this type of system. This research assumes that, for economic and safety reasons, industrial systems operate by default in closed-loop to ensure stability and desired performance. Therefore, a methodology is introduced to identify the open-loop transfer function of industrial plants, based on data obtained by signal measurement, of the industrial process operating in closed-loop, denominated Two-Stage Method. The identified model is used to design a controller that meets the performance criteria defined by the FTCS instead of the traditional control system, designed for a specific operating point regardless of the fault acting in the system. For experimental evaluation, an industrial fluid pumping bench was used, developed at the Automation and Control Laboratory of Federal University of Pará (UFPA). A passive FTCS was designed using robust control technique based on parametric uncertainties. For that end, it was used a set of uncertain models, obtained by parametric identification, considering a desired operating range for the test plant, with the system operating under both normal and fault conditions. Performance indices were calculated in order to quantitatively evaluate the performance of the FTCS monitored system, with the results obtained for the system operating without the FTCS (using classical controller). The results show the good performance of the proposed methodology.